INFLUENCE OF STORAGE TIME OF Monacrosporium thaumasium PELLETS ON THE PREDATION OF INFECTIVE LARVAE OF SHEEP GASTROINTESTINAL NEMATODES - SILVA, F. F.; COSTA, P. W. L.; BEZERRA, R. A.; SILVA, S. S.; SILVA, N. I. S.; LIMA, J. D. S.; FEITOSA, T. F.; BRAGA, F. R.; ARAÚJO, J. V.; VILELA, V. L. R. (Ars Veterinaria, 2018)
The objective of this study was to evaluate the influence of the storage time of Monacrosporium thaumasium pellets on the predation of infective larvae of sheep gastrointestinal nematodes in the semi-arid area of Paraíba, Northeast Brazil. 24 sheep with zero in the count of eggs per gram of faeces – EPG, were divided into four experimental groups: Group I, 3 g/10 kg live weight M. thaumasium pellets - 36 months of storage, single dose; Group II, 3 g/10 kg live weight M. thaumasium newly produced, single dose; Group III, 3 g/10 kg live weight pellets without fungi; and Group IV (control group) did not receive pellets. Every 24 h, up to 120 h, the faeces of the animals were collected and submitted to the laboratory for analysis. Fifteen grams of faeces were weighed from each animal and five grams of expanded vermiculite were added to produce the coprocultures. Subsequently, 1000 larvae (L3) sheep trichostrongilides were added, and larval recovery was performed after 7 days. Predation of larvae in Group I (M. thaumasium - 36 months) did not differ significantly (p > 0.01) from Group II (M. thaumasium - recent), with reductions of 75% and 79%. Both groups reached peak predation to larvae at 72 h. The helminth genus most recovered in the coprocultures was Haemonchus sp. The data indicate that the 36-month stocking period of M. thaumasium pellets in alginate matrix did not influence the efficacy of predation of infective larvae of sheep gastrointestinal nematodes, with fungal activity in the faeces up to 96 hours after administration to the animals.